Ocular Complications of Intravesicular BCG Treatment for Bladder Carcinoma. (2nd January 2022) - Ceylan, Osman Melih; Durukan, Ali Hakan; Uysal, Yusuf; Ozge, Gokhan; Dogan, Deniz; Bozlar, Ugur
ABSTRACT: Purpose: To report genital and ocular Bacillus Calmette-Guérin (BCG) infection as a rare complication of intravesical BCG immunotherapy. Methods: We report a patient with bladder carcinoma who developed penile and ocular BCG infection. Medical history, clinical features, imaging findings, histopathological evaluation, and response to treatment clinched the diagnosis. Result: Granulomatous inflammation was noted on histopathological evaluation of lung and cutaneous lesion of the penis. The left eye with choroidal tubercle and tractional retinal detachment involving fovea underwent pars plana vitrectomy. After silicone removal, best-corrected visual acuity was 20/100 and patient received anti-TB regimen for 12 months. At 1 year follow-up, the choroidal tuberculoma was found to have completely resolved and the ocular status was stable. Conclusions: Though there are other reported cases of BCG infection secondary to intravesical BCG instillation noted in the literature, penile granuloma accompanying with choroidal tubercle is an uncommon form among these complications.